REDESIGN APLIKASI LAYANAN TUNGGU MENGGUNAKAN METODE LEAN UX - Try Hafsani, Yuke; Anjeli, Saiba; Efendi, Yoyon (Program Studi Teknologi Rekayasa Internet, Politeknik Negeri Lampung, 2026)
The Tunggu Service Application is a digital service application owned by the Population and Civil Registration Service (Disdukcapil) of Pekanbaru City which not only provides population administration services, but also various supporting features that make it easier for the public to access services digitally. This application is designed to increase the ease of service access for the public without having to come directly to the Disdukcapil office. The existence of the Waiting Service application is expected to increase the effectiveness of the service, reduce queues in the office, and encourage the utilization of digital services in the government environment. However, based on the results of initial observation and initial testing to users, the appearance and usage flow of the Waiting Servic application is not fully in accordance with the user's needs. Some users stated that they had difficulty in understanding the flow of the service and assessing that the appearance of the application still needed to be improved. This condition has an impact on the user's comfort in using the application. Therefore, it is necessary to redesign the User Interface (UI) and User Experience (UX) so that the application can be used more easily and in accordance with the user's needs. The Lean UX method was chosen in this study because it focuses on user satisfaction through an iterative, collaborative, and user feedback-based design process. Based on the results of analysis, implementation, and evaluation, this research produces a final prototype which is a combination of prototype A and prototype B that has been validated in terms of appearance, functionality, as well as criticism and suggestions from users and technical parties. Prototype A was chosen for 3 features and prototype B was chosen for 3 other features. On the home page selected design B with a percentage of 57%, the service submission page selected design A with a percentage of 76%, and the schedule selection page selected design B with a percentage of 62%. In addition, the research results show that the proposed interface design has consistency in the use of colors, typography, icons, and layouts, as well as providing a user experience that is easier to understand in accessing features and information as needed. The final design was tested using the Usability Testing method to measure the level of ease of use and user acceptance of the proposed Layanan Tunggu application design.